2009
DOI: 10.1089/thy.2008.0371
|View full text |Cite
|
Sign up to set email alerts
|

Results of Rosiglitazone Therapy in Patients with Thyroglobulin-Positive and Radioiodine-Negative Advanced Differentiated Thyroid Cancer

Abstract: Our findings suggest that rosiglitazone therapy may induce radioiodine uptake and reduce serum thyroglobulin levels in some patients with differentiated thyroid cancer but this did not result in clinically significant response on long-term follow-up. Moreover, no patients had response to rosiglitazone therapy by anatomic imaging studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 21 publications
0
51
0
Order By: Relevance
“…Grade 4: myocardial infarction and small-cell lung cancer Capdevila et al (2012) Grade 3: HFS (20) been studied as well, mainly comprising rosiglitazone, vorinostat, thalidomide, celecoxib, and selumetinib (Mrozek et al 2006, Ain et al 2007, Kebebew et al 2009, Woyach et al 2009, Ho et al 2013. Though most of them exhibited modest efficacy, selumetinib, a MAPK kinase (MEK) 1 and MEK 2 inhibitor, increased the uptake of iodine-124 in 12 of the 20 patients (60%).…”
Section: Discussionmentioning
confidence: 99%
“…Grade 4: myocardial infarction and small-cell lung cancer Capdevila et al (2012) Grade 3: HFS (20) been studied as well, mainly comprising rosiglitazone, vorinostat, thalidomide, celecoxib, and selumetinib (Mrozek et al 2006, Ain et al 2007, Kebebew et al 2009, Woyach et al 2009, Ho et al 2013. Though most of them exhibited modest efficacy, selumetinib, a MAPK kinase (MEK) 1 and MEK 2 inhibitor, increased the uptake of iodine-124 in 12 of the 20 patients (60%).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study of thiazolidinediones showed an increase in differentiation in the human thyroid follicular carcinoma cell lines [37], and in vivo studies of thiazolidinediones reported that a quarter of patients with radioiodine negative DTC achieved a positive radioiodine scan [38,39], in 1 of these studies, no CR or PR was obtained at 3 months after treatment according to RECIST criteria [39]. Several studies have reported that HDAC inhibitors induced sodium iodide symporter gene expression and radioiodine uptake [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…However, the same group reported somewhat disappointing results several years later. Although rosiglitazone induced an increase in iodine uptake or decrease in serum Tg to some degree in 5/20 patients, a clinically significant response such as CR (complete response) or PR was not observed [46]. Thus, the clinical trials so far have not demonstrated very satisfactory results, but selection of more specific indications may be an answer.…”
Section: Pparγ Agonistsmentioning
confidence: 97%
“…So far, rosiglitazone is the only drug that has been tried in thyroid cancer patients [45][46][47][48][49]. However, as troglitazone was reported to be more effective than any other thiazolinedione in a cell study [43], appropriate drug selection will be an issue.…”
Section: Pparγ Agonistsmentioning
confidence: 99%